Management of patients with acute nonspecific low back pain - A. I. Isaikin; V. A. Golovacheva; I. V. Kuznetsov (Неврология, нейропсихиатрия, психосоматика, 2015)
The paper describes an observation of a female patient with acute non-specific low back pain (LBP). It gives current recommendations for the treatment of acute LBP and evaluates the clinical efficiency of these methods. The management of patients with acute nonspecific LBP encompasses: 1) correct information about the nature and prognosis of the disease; 2) recommendations for daily activities; 3) a short-term rational therapy with paracetamol, nonsteroidal anti-inflammatory drugs (NSAIDs), and/or myorelaxants. The role of NSAIDs, ketorol in particular, in treating patients with acute nonspecific LBP is discussed.